Exploring the Role of Resilience in Mitigating Stress and Enhancing Mental Health among University Students - Jan, Afreen; Ahmad, Amir (International Journal of Psychosocial Rehabilitation, 2019)
The study aimed to explore the role of resilience in mitigating stress and enhancing mental health among university students. The sample comprised 98 university students aged between 25-35, enrolled in diverse undergraduate, post graduate, and PhD courses from various districts of Kashmir. The instruments utilized for assessing perceived stress, resilience, and mental health were the 10-item Perceived Stress Scale developed by Cohen et al. (1993), the 6-item Resilience Scale by Smith et al. (2008), and the 12-item General Mental Health Questionnaire developed by Goldberg and Williams (1988). The findings revealed a significant negative correlation between perceived stress and brief resilience, as well as a strong negative correlation between perceived stress and mental health. Additionally, a moderate positive correlation was observed between brief resilience and mental health. Gender differences were assessed for all three variables, although females are on the slightly higher end in terms of mean differences with respect to perceived stress and brief resilience, but the differences are small to be called statistically significant.